2016
DOI: 10.5194/acp-16-2185-2016
|View full text |Cite
|
Sign up to set email alerts
|

Unexpectedly high ultrafine aerosol concentrations above East Antarctic sea ice

Abstract: Abstract. Better characterisation of aerosol processes in pristine, natural environments, such as Antarctica, have recently been shown to lead to the largest reduction in uncertainties in our understanding of radiative forcing. Our understanding of aerosols in the Antarctic region is currently based on measurements that are often limited to boundary layer air masses at spatially sparse coastal and continental research stations, with only a handful of studies in the vast sea-ice region. In this paper, the first… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
78
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(94 citation statements)
references
References 71 publications
15
78
1
Order By: Relevance
“…The CN 2.5−10 /CN 10 ratio is the parameter used to distinguish between particles newly formed from gas-to-particle conversion and background particles (Warren and Seinfeld, 1985;Humphries et al, 2015). Humphries et al (2016) also used the CN 2.5−10 /CN 10 ratio to distinguish the NPF days during a 52 d voyage in the East Antarctic sea-ice region because the number concentration data were more reliable than the size distribution data.…”
Section: Definition Of Npf Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CN 2.5−10 /CN 10 ratio is the parameter used to distinguish between particles newly formed from gas-to-particle conversion and background particles (Warren and Seinfeld, 1985;Humphries et al, 2015). Humphries et al (2016) also used the CN 2.5−10 /CN 10 ratio to distinguish the NPF days during a 52 d voyage in the East Antarctic sea-ice region because the number concentration data were more reliable than the size distribution data.…”
Section: Definition Of Npf Eventsmentioning
confidence: 99%
“…In order to understand the characteristics of the NPF, studies have been conducted in various regions including coastal, forest, mountainous, rural and urban sites (O'Dowd et al, 2002;Komppula et al, 2003;Yoon et al, 2006;Park et al, 2009;Kim et al, 2011;Rose et al, 2015;Bianchi et al, 2016;Kontkanen et al, 2017). In addition, studies on the NPF phenomenon have recently been conducted at various sites in the polar regions (Asmi et al, 2010;Järvinen et al, 2013;Kyrö et al, 2013;Park et al, 2004;Weller et al, 2015;Humphries et al, 2016;Nguyen et al, 2016;Willis et al, 2016;Barbaro et al, 2017;Dall'Osto et al, 2017). A NPF event occurring in the period between December 1998 and December 2000 at the South Pole was reported by Park et al (2004).…”
Section: Introductionmentioning
confidence: 99%
“…In a seminal review, Carslaw et al (2013) concluded that uncertainties in cloud radiative forcing are inter alia caused by uncertainties in natural emissions of dimethylsulfide (DMS) producing biogenic sulfur aerosol (i.e., MS − and nss-SO 2− 4 ) and sea spray. The radiation budget over the Southern Ocean is a particular challenge for current climate models, as they disturbingly underpredict the aerosol optical depth, pointing to a missing source of aerosols influencing cloud properties in this region (Bodas-Salcedo et al, 2014;Humphries et al, 2016). The competing role of biogenic sulfur (linked with phytoplankton presence) and otherwise sea salt aerosol (linked with stormy sea) in controlling cloudiness above the Southern Ocean is still up for debate (Meskhidze and Nenes, 2006;Korhonen et al, 2008;Quinn and Bates, 2011;Gras and Keywood, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, dedicated aerosol investigations within EPICA at Kohnen have demonstrated the conspicuous impact of a cyclone on aerosol transport: in the aftermath of an intense low-pressure system over the eastern Weddell Sea region in combination with a blocking highpressure ridge to the east in early January 2002 (Birnbaum et al, 2006), MS − and nss-SO 2− 4 aerosol entry showed an exceptional maximum . So far, a distinct impact of cyclones on aerosol concentrations has been frequently observed at coastal sites (e.g., Ito andIwai, 1981, for Syowa andPant et al, 2010, for Maitri), but only rarely on the Antarctic Plateau region (Hogan and Barnard, 1978, for the South Pole). In the most elaborate study about this topic, Pant et al (2010) reported an almost constant background aerosol concentration under calm conditions, while during the passage of cyclones coarse-mode sea salt aerosol increased by an order of magnitude and occasionally new particle formation could be detected in the aftermath of the storms.…”
Section: Introductionmentioning
confidence: 99%
“…Ocean is a challenge for current climate models, as they disturbingly under predict the aerosol optical depth, pointing to a missing source of aerosols influencing cloud properties in this region (Bodas-Salcedo et al, 2014;Humphries et al, 2016).…”
Section: Introductionmentioning
confidence: 99%